A Sensitive Potentiometric Sensor for Isothermal Amplification-Coupled Detection of Nucleic Acids - Kang-Ho Lee; Dongkyu Lee; Jongsu Yoon; Ohwon Kwon; Jaejong Lee (Sensors, 2018)
A disposable potentiometric sensor was newly developed for the amplification-coupled detection of nucleic acids. The hydrogen-ion is generally released during isothermal amplification of nucleic acids. The surface potential on the oxide-functionalized electrode of the extended gate was directly measured using full electrical circuits with the commercial metal-oxide semiconductor field-effect transistors (MOSFETs) and ring oscillator components, which resulted in cost-effective, portable and scalable real-time nucleic acid analysis. The current-starved ring oscillator changes surface potential to its frequency depending on the square of the variation in pH with a high signal-to-noise ratio during isothermal amplification. The device achieves a conversion rate of 20.5 kHz/mV and a detection resolution of 200 µV for the surface potential. It is demonstrated that the sensor successfully monitors in real-time isothermal amplification of the extracted nucleic acids from Salmonella pathogenic bacteria. The in situ variations in the frequency of the pH-sensitive sensor were compared with the results of both a conventional optical device and pH-meter during isothermal amplification.